2011
DOI: 10.1002/cctc.201100205
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Phosphate Coating on Aluminum Foams by Electrophoretic Deposition for Acidic Catalysis

Abstract: The electrophoretic deposition method has been applied for the formation of an amorphous zirconium phosphate layer on the surface of open‐cell aluminum foam. The aluminum foam was fully and uniformly covered by the zirconium phosphate layer with a good mechanical adherence to the support. The obtained composites were characterized by using XRD, SEM and nitrogen adsorption. The coated aluminum foams showed high catalytic activity in the dehydration of fructose to 5‐hydroxymethylfurfural. This method of foam coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In fact, the LGO conversion with sulfuric acid 11 did not produce FF, and the selectivity to HMF was high. A similar conclusion regarding the unfavorable catalytic role of Lewis acid sites over solid acid catalysts is apparent for the conversion of xylose to FF, 41 fructose to HMF, 42 and furfuryl alcohol to levulinic acid. 43 FF is likely formed by the catalysis of Lewis acid sites for removing alcohol functional group in the course of LGO pyranose ring opening to form furan ring.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
“…In fact, the LGO conversion with sulfuric acid 11 did not produce FF, and the selectivity to HMF was high. A similar conclusion regarding the unfavorable catalytic role of Lewis acid sites over solid acid catalysts is apparent for the conversion of xylose to FF, 41 fructose to HMF, 42 and furfuryl alcohol to levulinic acid. 43 FF is likely formed by the catalysis of Lewis acid sites for removing alcohol functional group in the course of LGO pyranose ring opening to form furan ring.…”
Section: ■ Results and Discussionsupporting
confidence: 58%
“…Electrophoretic deposition has been used to form an amorphous ZrP layer on the surface of open-cell Al foam. The surface area of the ZrP layer on the foam surface was 198 m 2 /g, which is higher than that of the uncoated foam, 89 m 2 /g, as a result of stabilization of the particles on the foam surface, preventing agglomeration [33]. Compared with other reported catalysts, ZrP catalysts are more selective for HMF in fructose conversion because of their inherent acid strength.…”
Section: Catalytic Dehydrationmentioning
confidence: 85%
“…An amorphous ZrP layer deposited on the surface of open-cell Al foam showed high catalytic activity in fructose dehydration to HMF [33]. The Al foam was fully and uniformly covered by the ZrP layer, with good mechanical adherence to the support.…”
Section: Catalytic Dehydrationmentioning
confidence: 99%
“…26 Previously, it was reported that excess of acidity leads to formation of several unwanted side products, and thus the yield of 5-HMF was decreased. 27 In spite of acidity the base matrix on which acid functional groups were located also contributed to substrate catalyst interactions. The controlled tuning of surface acidity on the specific backbone of a heterogeneous catalyst plays a significant role for the development of an efficient catalyst for the synthesis of 5-HMF.…”
Section: ■ Results and Discussionmentioning
confidence: 99%